Speech by Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin UniMAP's Vice Chancellor during the Indonesia-Malaysia-Thailand Growth Triangle (IMT – GT) Varsity Carnival 2009 - Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr. (Universiti Malaysia Perlis, 2010)
The event was held at UiTM's stadium, Arau, Perlis.